Capital Flows : Review of Experience with the Institutional View. (Policy Papers; Policy Paper, 2016)
Capital flows are an important aspect of the international monetary system. They provide significant benefits, both direct and indirect. At the same time, they also carry risks, and a key challenge for countries is how to harness the benefits while managing the risks. The institutional view on the liberalization and management of capital flows provides the Fund with a basis for consistent advice on policies related to capital flows. This paper reviews countries' experiences with handling capital flows in the period since the adoption of the IMF's institutional view in 2012. Based on the experience, it identifies a few areas in which the view would benefit from further clarification or elaboration.